Chromosomal and genomic analysis suggests single origin and high molecular differentiation of the B chromosome of Abracris flavolineata - Milani, Diogo [UNESP]; Gasparotto, Ana Elisa [UNESP]; Loreto, Vilma; Martí, Dardoa.; Cabral-De-mello, Diogo C. [UNESP] (Canadian Science Publishing, 2024)
Supernumerary chromosomes (B chromosomes) have been an intriguing subject of study. Our understanding of the molecular differentiation of B chromosomes from an interpopulation perspective remains limited, with most analyses involving chromosome banding and mapping of a few sequences. To gain insights into the molecular composition, origin, and evolution of B chromosomes, we conducted cytogenetic and next-generation sequencing analysis of the repeatome in the grasshopper Abracris flavolineata across various populations. Our results unveiled the presence of B chromosomes in two newly investigated populations and described new satellite DNA sequences. While we observed some degree of genetic connection among A. flavo-lineata populations, our comparative analysis of genomes with and without B chromosomes provided evidence of two new B chromosome variants. These variants exhibited distinct compositions of various repeat classes, including transposable elements and satellite DNAs. Based on shared repeats, their chromosomal location, and the C-positive heterochromatin content on the B chromosome, these variants likely share a common origin but have undergone distinct molecular differentiation processes, resulting in varying degrees of heterochromatinization. Our data serve as a detailed example of the dynamic and differentiated nature of B chromosome molecular content at the interpopulation level, even when they share a common origin.
Keywords: FISH; genome; population; repetitive DNAs; supernumerary chromosome